Parque Tema Turístico Y Educativo en el Desierto de la Tatacoa Complejo Astronómico Nacional de la Tatacoa (2022)
By developing a proposal that generates recognition and income for a Department like Huila and, in turn, for the municipality of Villavieja, through an arduous investigation, the construction of an astronomical and theme park in the Tatacoa Desert is proposed, taking into account the needs of the population, is viewed as a solution to adequate equipment infrastructure for astronomy. problems such as the lack of These actions are aimed at drawing the attention of tourists where they feel attracted and their visit is pleasant within all the possibilities offered by researchfocused astro nomy so that it is promoted through word of mouth and their social networks and thus attract each once again to tourists and visitors from all over the world.